The consequences of job crafting and engagement in the relationship between passion for work and individual performance of Portuguese workers - Vieira dos Santos, Joana; Gomes, Alexandra; Rebelo, Diana Filipe Saraiva; Lopes, Luis Felipe Dias; Moreira, Martiele Gonçalves; da Silva, Deoclécio Junior Cardoso (Frontiers in Psychology, 2023)
This study sought to relate the two types of work passion, harmonious passion and obsessive passion, to the organizational consequences of engagement, job crafting, and perceived individual job performance. This study was based on the Employee Work Passion Appraisal model and conducted to evaluate possible statistical associations of the dualistic approach of passion used as an antecedent on positive and negative organizational outcomes (engagement, job crafting, and perceived individual job performance). The data collection and analysis for this study were accomplished by a transversal and quantitative study design. A non-probabilistic method was used to select a convenience sample composed by 305 Portuguese workers and was collected online from March to October 2020. The proposed hypotheses were evaluated using partial structural equation models. Overall, the results supported the proposed hypotheses and showed that harmonious passion positively affected organizational outcomes and obsessive passion negatively affected these outcomes; notably, our findings also revealed high individual performance, high obsessive passion, and consequently, a significant increase in structural labor resources, a significant decrease in harmful labor demands, and high absorption.